Designing room-temperature multiferroic materials in a single-phase solid-solution film. (9th August 2016) - Mao, H J; Song, C; Cui, B; Peng, J J; Li, F; Xiao, L R; Pan, F
Abstract: The search for multiferroic materials with simultaneous ferroelectric and ferromagnetic properties in a single phase at room temperature continues to be fuelled from the perspective of developing multifunctional devices. Here we design a single-phase multiferroic La0.67 Sr0.33 MnO3 -BaTiO3 film, which possesses epitaxial single-crystal and solid-solution structure, high magnetic Curie temperature ( 640 K) as well as switchable ferroelectric polarization. Moreover, a notable strain-mediated magnetoelectric coupling at room temperature in the way of modulating the magnetism with an external applied voltage is also observed. The synthetic solid-solution multiferroic film may open an extraordinary avenue for exploring a series of room-temperature multiferroic materials.